Pengaruh Motivasi Kerja, Kedisiplinan Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai: Studi di Badan Pertanahan Nasional Klaten - Syahrul Nur Fauzi; Kusdiyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Employee performance in carrying out work influences various things such as the condition of employee behavior while working. Employee performance greatly influences discipline, motivation and the work environment, this can be seen directly in the work results. A very important problem is to be able to know significantly about employee performance so that they can be more productive. This research aims to find out how significantly influences motivation, discipline and the environment on performance, especially in the BPN Office of Klaten Regency. The objects of this research are employees of the Klaten Regency BPN office. This research took a sample of 125 employees using the Solvin formula. This research uses two data, namely primary data and secondary data. The data collection method uses a questionnaire, then it is measured using a Likert scale of one to five and Structural Equation Model (SEM) analysis via partial least squares (Smart-PLS). And the research results will show how significant the influence of motivation, environment and discipline is on the performance of Klaten Regency BPN Office employees.